Enhancing Public Safety Through Dynamic Switching Between Unicast and Broadcast Transmission Modes in Cellular Networks - Mohamad Younes; Yves Louet (IEEE Access)
This article proposes new directions to enhance spectrum resource allocation in dense cellular networks, especially during massive dissemination of public safety alerts. We are conducting a comparative study to identify the most efficient transmission mode among the following options: conventional Unicast (UC) mode, UC mode combined with beamforming, Point-To-Multipoint (PTM) single-cell broadcast mode, and multi-cell broadcast mode via a Single-Frequency Network (SFN). In the absence of standardized norms for determining the optimum mode, we are developing a model to establish a threshold for the number of users per base station, at which point each broadcast mode between SFN and PTM becomes more spectrally efficient than conventional UC and UC with beamforming. Our contribution includes an in-depth simulation study to assess the sensitivity of this threshold to the variability of system parameters under different scenarios and conditions. This analysis will support informed decisions on the optimal transmission mode, thereby improving public safety in critical circumstances.